A Randomized, Controlled, Evaluator-Blinded, Multi-Center Study of Hyaluronic Acid Filler Effectiveness and Safety in Lip Fullness Augmentation. Issue 4 (April 2021) - Weiss, Robert; Beer, Kenneth; Cox, Sue E.; Palm, Melanie; Kaufman-Janette, Joely; Bassichis, Benjamin; Biesman, Brian; Joseph, John; Almegård, Birgitta; Nilsson, Anna; Edwartz, Carolina
Abstract : BACKGROUND: HARK was recently approved in the US for lip augmentation and correction of upper perioral rhytids. OBJECTIVE: To demonstrate noninferiority of HARK versus a control (HAJV ) in lip fullness augmentation at Week 8 after last injection (blinded evaluation). Secondary objectives were to evaluate the effectiveness and safety of HARK in lip fullness augmentation and correction of upper perioral rhytids. METHODS AND MATERIALS: Treatment with HARK or control (randomized 2:1) was administered on Day 1 in this 48-week, evaluator-blinded study with optional touch-up at Week 4. Primary endpoint was change from baseline to Week 8 in lip fullness. Secondary endpoints included lip fullness, wrinkle severity, aesthetic improvement, subject satisfaction, adverse events, and local tolerability (subject diary entries). RESULTS: The primary objective was met; HARK was noninferior to control in lip fullness augmentation at Week 8. Lip fullness and wrinkle severity improvement persisted at Week 48, and was accompanied by high aesthetic improvement and subject satisfaction scores. The mean volume of HARK injected was approximately 20% lower than control. Treatment-related adverse events and local tolerability symptoms were predominantly mild and transient. CONCLUSION: HARK was noninferior to control in lip fullness augmentation at Week 8, well-tolerated, and effective throughout this 48-week study. Abstract : Supplemental Digital Content is Available in the Text.